Factors Of Green Logistics Implementation In Malaysia A Study On A Global Logistics Provider - Lew, Rose Ai Fen (2017)
Green logistics has become the newest trend in doing business that is not just economy and social sustainable for the logistics organizations but is also environment sustainable. As the world ecology is becoming worse due to globalization and industrialization with the rising temperature and sea levels, many global logistics companies are applying green logistics as it helps mitigate climate change by reducing carbon emissions. The objectives of this research have been threefold. The first was to identify the factors which need to be considered in green logistics implementation for global logistics company that operates in Malaysia. The second was to examine the ways that a global logistics company operating in Malaysia could take when implementing green logistics. The third was to construct a green logistics model that could contribute empirically to the Malaysian logistics industry. Primary data was collected using 30 semi-structured open-ended interviews and participant observation (observer-asparticipant). Secondary data regarding logistics, green logistics (implementation factors and ways) and business sustainability were obtained from various literatures. Findings indicated that there were gaps between the chosen global logistics company which is DB Schenker Malaysia and various literatures findings on green logistics in terms of the internal and external implementation factors as well as on the ways to implement green logistics. A green logistics model was then constructed to close the gaps and provide as a guide for logistics managers and the like especially in Malaysian logistics industry. The green logistics model developed is general enough for further investigation by testing its feasibility in Malaysian logistics industry or any other relevant industries. The model can also be evaluated by comparing with other similar designs by other researchers or by extending its application to other problems.